PUBLIC - PRIVATE PARTNERSHIP IN SERBIA: LEGAL FRAMEWORK AND THE POSSIBILITY OF ITS ESTABLISHMENT IN RURAL AREAS AND AGRICULTURE - Rapaijć, Milan; Purić, Sveto; Purić, Jelena (Economics of Agriculture, 2013)
The aim of this paper is to present some legal solutions from this Law, particularly the legal forms of public-private partnership foreseen by the Law: institutional and contractual. One of the most significant positive results of public-private partnership in the future should be its application in rural areas and agriculture in order to support the natural predispositions, that is advantages of the Republic of Serbia in certain economic branches (particularly in agriculture). The authors applied the legal method in combination with the comparative. Also, it was applied case study regarding to the establishment of public-private partnerships in agriculture. One of the purposes of this paper is to influence on the scientific community to prefer public-private partnership, in requirements for encouraging agricultural production, then pure privatization (the purchase of large agricultural areas). Land is the national treasures and should be owned by domestic residents and legal entities.